Johannes Brusila, Bruce Johnson and John Richardson, eds. 2016. Memory, Space, Sound. (17th December 2018) - Ahlers, Michael
Abstract : Johannes Brusila, Bruce Johnson and John Richardson, eds. 2016. Memory, Space, Sound. Bristol: Intellect. ISBN 978-1-78320-602-5 (hbk), 978-1-78320-603-2 (ePDF), 978-1-78320-604-9 (ePub). 231 pp.